Multiscale corrosion analysis of superhydrophobic coating on 2024 aluminum alloy in a 3.5 wt% NaCl solution. (June 2020) - Sebastian, Divine; Yao, Chun-Wei; Lian, Ian
Abstract: Abstract : In this work, a facile superhydrophobic coating for 2024-T3 aluminum alloy is developed and characterized. The corrosion resistance of the coating was analyzed. The results showed that the coating has high polarization resistance and a low corrosion rate. Furthermore, a micro/nanoscale investigation about the interaction between substrates and the corrosive environment was carried out using the in situ atomic force microscope technique. The change in surface topography was monitored for both the bare aluminum alloy substrate and the superhydrophobic aluminum alloy. The results showed that the coating retained surface features indicated that the coating has excellent corrosion resistance.